Analysis of Factors Afecting Coffee Production in Bandung Regency - Nugroho Sumarjiyanto Benedictus Maria; Aqshal Averiel Albiyand (Universitas Diponegoro, 2023)
This study aims to analyze the effect of factors of production on the level of coffee production in the Bandung Regency during a pandemic. The selected variables are capital, land area, labor, and fertilizer. The population in this research is coffee farmers in Bandung Regency. The sample was selected through simple random sampling with the results of as many as 100 respondents from coffee farmers from villages in Bandung Regency. This type of research uses quantitative methods with a descriptive approach. The data obtained and collected were then analyzed through multiple linear regression using Statistical Package for the Social Sciences (SPSS) version 25. The results of this study indicate that only capital, land, and fertilizer partially have a positive and significant impact on coffee production in Bandung Regency during the pandemic. Labor variables partially have no significant impact on coffee production in Bandung Regency during the pandemic. Simultaneously capital, land area, labor, and fertilizer had a significant impact on coffee production in Bandung Regency during the Pandemic. This could encourage future research in the coffee plantation sector that uses this variable to support strategic policy.